Membrane potential imaging in the nervous system methods and applications - Canepari, Marco; Zecevic, Dejan; SpringerLink (Online service). (New York, NY Springer, 2011)
Membrane Potential Imaging in the Nervous System: Methods and Applications describes optical techniques to monitor neuronal membrane potential signals. The knowledge upon which voltage-imaging technique is based was generated over several decades and the aim of this book is to provide a single comprehensive source of information on different types of voltage-imaging techniques, including overviews, methodological details, examples of experimental measurements, and future developments. The book is structured in five sections, each containing several chapters written by experts and major contributors to particular topics. The volume starts with a historical perspective and fundamental principles of membrane potential imaging and continues to cover the measurement of membrane potential signals from dendrites and axons of individual neurons, measurements of the activity of many neurons with single cell resolution, monitoring of population signals from the nervous system, and concludes with the overview of new approaches to voltage-imaging. Membrane Potential Imaging in the Nervous System is targeted at all scientists interested in this mature but also rapidly expanding imaging approach.
Historical overview and general methods of membrane potential imaging -- Design and use of organic voltage sensitive dyes -- Imaging submillisecond membrane potential changes from individual regions of single axons, dendrites and spines -- Combined voltage and calcium imaging and signal calibration -- Use of fast-responding voltage-sensitive dyes for large-scale recording of neuronal spiking activity with single-cell resolution -- Monitoring integrated activity of individual neurons using FRET-based voltage-sensitive dyes -- Monitoring population membrane potential signals from neocortex -- Monitoring population membrane potential signals during functional development of neuronal circuits in vertebrate embryos -- Imaging the dynamics of mammalian neocortical population activity in-vivo -- Imaging the dynamics of neocortical population activity in behaving and freely moving mammals -- Monitoring membrane voltage using two-photon excitation of fluorescent voltage-sensitive dyes -- Random-access multiphoton microscopy for fast three-dimensional Imaging -- Second harmonic imaging of membrane potential -- Genetically encoded protein sensors of membrane potential.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Membranes (Biology) -- Imaging; Cellular signal transduction -- Measurement; Neural conduction -- Measurement